National survey addressing the information needs of primary care physicians: Side effect management of patients on androgen deprivation therapy - Soeyonggo, Tony (Canadian Medical Association, 2014)
OBJECTIVE: Androgen deprivation therapy (ADT) is a common treatment for prostate cancer with numerous side effects. We assess primary care physicians’ (PCPs) knowledge of ADT side effects and their interest in increasing their knowledge in this area. METHODS: A list of active Canadian PCPs was obtained using the Canadian Medical Directory. A cross-sectional survey was distributed to 600 randomly selected physicians. We collected PCPs’ demographic information, experience with ADT management, knowledge regarding ADT side effects and desired sources for obtaining knowledge on ADT management. RESULTS: In total, we received 103 completed questionnaires. Of these, 89% of PCPs had patients on ADT. One-third of respondents prescribed ADT and over half of them administered ADT annually. Thirty-eight percent felt their knowledge of ADT side effects was inadequate and 50% felt uncomfortable counselling patients on ADT. Many PCPs were less familiar with the incidence of functional side effects of ADT (i.e., hot flashes, fatigue and erectile dysfunction) compared to life-threatening side effects (i.e., cardiovascular events, metabolic syndrome, fractures). In terms of increasing their knowledge of ADT side effects, 82% of PCPs would use educational resources if they were available (52% and 32% preferred continued medical education [CME] events and educational pamphlets, respectively). CONCLUSIONS: PCPs play an important role in managing ADT side effects. There is poor awareness of the prevalence of ADT side effects, and many are uncomfortable in managing these side effects. These areas may be addressed through CME programs and educational pamphlets.